A posteriori error estimation of H1 mixed finite element method for the Benjamin-Bona-Mahony equation - Sabarina Shafie (N/A, 2017)
A posteriori error estimation of H1 mixed finite element method for the Benjamin-Bona-Mahony equation by Sabarina Shafie